2022
DOI: 10.22541/au.165694329.91407425/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unhealthy herds and the predator spreader: understanding when predation increases disease incidence and prevalence

Abstract: Disease ecologists now recognize the limitation behind examining host-parasite interactions in isolation: community members – especially predators – dramatically affect host-parasite dynamics. Although the initial paradigm was that predation should reduce disease in prey populations (“healthy herds hypothesis”), researchers have realized that predators sometimes increase disease in their prey. These “predator-spreaders” are now recognized as critical to disease dynamics, but empirical research on the topic rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…We found only few direct effects of herbivores on the pathogens. Sheep directly increased biotrophic pathogen load, in line with findings for other mammalian grazers (Zhang et al., 2020) and studies in other systems (Richards et al., 2023) showing, for instance, that coral predators can increase disease through wounding and vectoring pathogens (Renzi et al., 2022). However, sheep grazing only directly facilitated the biotrophs, which might benefit especially from wounding (as shown for snail‐fungal interactions, Silliman & Newell, 2003), as they often consumed the upper parts of grass leaves (Liu, Duan, et al., 2021).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We found only few direct effects of herbivores on the pathogens. Sheep directly increased biotrophic pathogen load, in line with findings for other mammalian grazers (Zhang et al., 2020) and studies in other systems (Richards et al., 2023) showing, for instance, that coral predators can increase disease through wounding and vectoring pathogens (Renzi et al., 2022). However, sheep grazing only directly facilitated the biotrophs, which might benefit especially from wounding (as shown for snail‐fungal interactions, Silliman & Newell, 2003), as they often consumed the upper parts of grass leaves (Liu, Duan, et al., 2021).…”
Section: Discussionsupporting
confidence: 77%
“…We focused on vertebrate herbivores and found that sheep grazing increased biotrophic pathogens, while cattle grazing decreased biotrophic and necrotrophic pathogen load. Theory and some empirical work suggest that herbivores could regulate disease in host populations (Hudson et al., 1992; Liu, Mipam, et al., 2021; Packer et al., 2003), however the impacts of herbivores will depend on how they alter various aspects of community structure and the opposite pattern is also possible (Richards et al., 2023). Our approach to disentangle direct and indirect effects, combining structural equation modelling and a manipulative experiment to test particular pathways, was able to identify the mechanisms by which large grazers affected foliar pathogens and revealed that sheep and cattle affected pathogen groups via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation